Animal welfare dilemma: are we chikened-out? - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2008)
The concern on animal welfare has risen since decades ago. It has generated public interest and become a hot debate ever since the British MP Richard Martin, who was also an Irish politician and animal rights activist bravely called out through Parliament offering protection from cruelty to cattle, horses and sheep as its central concern in 1822. Earning himself the nickname Humanity Dick, he also emphasised on human morality and humane behaviour.